Optimization approach for the mesialization of lower molars: a case report - Montilla-Puente, Virginia Beatriz; Martínez-Morales, María Valentina; Tomich-Biber, Dayanna (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Premature molar loss results in inclination of teeth adjacent to the edentulous gap, uneven marginal ridges, posterior collapse of bite, and atrophy of the residual bone width. The orthodontic treatment aimed at closing post-extraction spaces, is one possible treatment plan. However, in many cases this movement is compromised by the collapse of cortical plates and the decrease of the osseous corridor. Due to this problem, flexicorticotomy may be considered as an alternative in the mesialization of molars to improve residual bone width and to accelerate orthodontic movement. A 22-year-old female patient underwent extraction of the right mandibular first molar. A flexicorticotomy was performed to accelerate the mesial movement of teeth number 37 and 38, using a miniscrew for absolute anchorage. This technique helped mesialize teeth number 37 and 38, attaining a stable class I relationship, thus finding an orthodontic solution to a problem that was historically treated only prosthetically. In conclusion, this technique facilitates the mesial movement of molars, reaching treatment goals more effectively, and saving costs by avoiding further prosthetic treatment.